2009
DOI: 10.1017/s0007114509992844
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and growth requirements for nitrogen, lysine and methionine and their utilisation efficiencies in juvenile black tiger shrimp,Penaeus monodon, using a factorial approach

Abstract: We used a factorial approach to distinguish maintenance from growth requirements for protein, lysine and methionine in the black tiger shrimp, Penaeus monodon. Juvenile P. monodon (initial weight 2·4 g) were fed during 6 weeks one of ten semi-purified diets based on casein and purified amino acids (AA) as N source. The diets contained four levels of crude protein (CP, from 5 to 54 % DM diet) with two levels (% CP) of lysine or methionine (normal or 30 % deficient). Requirements were determined using linear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 64 publications
6
35
1
1
Order By: Relevance
“…Thus, the toxic effects of free gossypol may not be recognized as the main reason for the growth depression of shrimps. On the other hand, the methionine levels in the experimental diets were below the recommended requirement for shrimps by Richard, Blanc, Rigolet, Kaushik and Geurden (). The shortage in methionine was more conspicuous in diets with high FM substitution levels (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the toxic effects of free gossypol may not be recognized as the main reason for the growth depression of shrimps. On the other hand, the methionine levels in the experimental diets were below the recommended requirement for shrimps by Richard, Blanc, Rigolet, Kaushik and Geurden (). The shortage in methionine was more conspicuous in diets with high FM substitution levels (i.e.…”
Section: Discussionmentioning
confidence: 64%
“…The Pm is also distinctly different between the two genotypes, but not between the two diets. By comparison, a Pm of 0.57 g kg À0.7 day À1 can be derived from the work of Richard et al (2010) for the same species, which is less than the wild-type shrimp from Australia, but higher than that of the selected genotype. However, the Pm of the wild-type shrimp (0.78-0.95 g kg À0.7 day À1 ) is considerably higher than most fish species.…”
Section: Figurementioning
confidence: 99%
“…The search for fish meal substitutes and alternative dietary protein sources has become an international research priority (Lee, 2002). Many studies have shown that the requirement of lysine in crustacean such as shrimp ranged from 3.8% to 5.8% of dietary protein (Fox et al, 1995;Millamena et al, 1998;Teshima et al, 2002;Richard et al, 2010;Xie et al, 2012;Palma et al, 2013). However, there were only a few studies on essential amino acid (EAA) requirement for marine and freshwater crabs (Ye et al, 2010).…”
Section: Introductionmentioning
confidence: 99%